Reconstituting the concepts of sustainable stormwater management - Musa, Mohd Faiz; Zen, Ismawi; Tukiman, Izawati (2013)
Even though various sustainable storm water managements are available, there is less clear discussion and classification of its concepts. Besides, little discussion on the relationship of the concepts with the hydrology cycle made the implementation of storm water management less successful in managing the problem caused by storm water such as flash flood and water pollution. Hence, this research aims to review the concepts of sustainable storm water management. Two objectives formulated are (i) to identify the concepts of sustainable stormwater management, and (ii)to identify any relationship of the identified concepts with other factors in sustainable storm water management. Online journal, forum discussion and e-mail interview were used as methods of data collection in this qualitative research. Six steps of descriptive comparative analysis were used to analyse the data. Consequently, the researcher had identified 11 concepts and listed the concepts in priority order. The 11 concepts are conservation of watershed, compact urban form, retain stormwater on site, treatment train, green network, harvest and reuse rainwater, redevelopment, streetscape ecosystem and restoration. The identified concepts were listed in priority order based on relationship with 7 hydrology cycles which are interception, infiltration, surface runoff, depression storage, evapotranspiration, groundwater flow and interflow. The concepts were analysed with hydrology cycles is because to ensure the sustainability factors in outlining the concepts to manage the storm water.